Herbal Wisdom and Practical Solutions: A Comparative Study of Abdominal Pain and Acute Intestinal Obstruction Treatments in versified Ibn Tufail’s Al ‘Urjuzah Fi Al Tibb and Other Classical Islamic Medicine Texts with emphasis on Posology - Adnane, Mouhssine; Benjelloun, El Bachir (DELTOS, 2025)
From the ninth to the nineteenth century, didactic poetry in the Islamic world encompassed a wide array of subjects, including theology, Qur’ānic studies, jurisprudence, history, logic, algebra, medicine, and agriculture. These poetic forms were crafted to engage audiences while effectively preserving and transmitting knowledge. Medieval Arabic poetry also explored the ethical, social, and humanitarian dimensions of medical care, as seen in works like the 13th-century bibliographic encyclopaedia by Ibn Abi Usaibia, which contains numerous quotations reflecting these themes. ...